WAIS Divide Sonic Log Data - Anandakrishnan, Sridhar; Kluskiewicz, Dan; Matsuoka, Kenichi; McCarthy, Michael; Waddington, Edwin D. (IEDA: US Antarctic Program Data Center, 2014)
This data set contains a record of speeds for vertically-propagating compression-waves measured throughout the depth of ice that surrounds the WAIS-D borehole. Multiple logs provide redundant measurements for all depths. Data for individual wave-speed measurements were included, as well as 3 m running averages for each log. A Takeaway Profile that represents our interpretation of the combined data set is also included.